2021
DOI: 10.33002/nr2581.6853.040410
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Agricultural Crop Productivity among Smallholder Households in Haramaya Distinct, Eastern Ethiopia

Abstract: The agricultural crop is a backbone in Ethiopia since the country's economy is mainly dependent on agriculture, which is dominated by subsistence smallholder farmers who are partially integrated into the market. The objective of this study was to identify the determinants of crop productivity among smallholder farmers in Haramaya distinct, Eastern Ethiopia. A two-stage random sampling procedure was employed to detect a sample containing 260 smallholder households in the study area. Data was collected through s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 183 publications
1
0
0
Order By: Relevance
“…This is probably the case since farmers who own big farms typically benefit from economies of scale when purchasing their inputs and selling their output, which lowers the unit cost. The outcomes are consistent with those of Nuno and Baker (2021).…”
Section: Identified Climate Smart Agricultural Techniques Adopted The...supporting
confidence: 80%
“…This is probably the case since farmers who own big farms typically benefit from economies of scale when purchasing their inputs and selling their output, which lowers the unit cost. The outcomes are consistent with those of Nuno and Baker (2021).…”
Section: Identified Climate Smart Agricultural Techniques Adopted The...supporting
confidence: 80%
“…High farm households' size in some cases may translate to high family labour for improved production. Nuno and Baker (2021) found that an increase in the number of economically active members in farm households enhances the overall productivity of the household. Alabi and Safugha (2022) reported that labour input constitutes a significant factor influencing crop production and output.…”
Section: Socioeconomic Factors Influencing Production Of African Yam ...mentioning
confidence: 99%
“…This is followed by handling the sub system of farm, to practice better farming than the current practices, include fertilizer application in particular and maintenances of crop, such as watering and pruning the mango trees. The applications are believed to increase production in quantity as well as in quality (Liliane and Charles, 2020;Nuno and Baker, 2021;Sadras et al, 2016).…”
Section: The Sub System Of Supporting Servicementioning
confidence: 99%